Medical costs associated with cardiovascular events among high-risk patients with hyperlipidemia - Bonafede MM; Johnson BH; Richhariya A; Gandra SR (Dove Medical Press, 2015)
Machaon M Bonafede,1 Barbara H Johnson,1 Akshara Richhariya,2 Shravanthi R Gandra2 1Outcomes Research, Truven Health Analytics, Cambridge, MA, USA; 2Global Health Economics, Amgen, Thousand Oaks, CA, USA Objectives: This study descriptively examined acute and longer term direct medical costs associated with a major cardiovascular (CV) event among high-risk coronary heart disease risk-equivalent (CHD-RE) patients. It also gives a firsthand look at fatal versus nonfatal CV events. Methods: The MarketScan® Commercial Claims and Encounters Database was used to identify adults with a CV event in 2006–2012 with hyperlipidemia or lipid-lowering therapy use in the 18 months prior to one of the following inpatient CV events: myocardial infarction, ischemic stroke, unstable angina, transient ischemic attack, percutaneous coronary intervention, or coronary artery bypass graft (CABG). Patients were required to have a preindex diagnosis of at least one of the following: peripheral arterial disease, abdominal aortic aneurysm, carotid artery disease, or diabetes. A subset analysis was conducted with patients with data linkable to the Social Security Administration Master Death File. Direct medical costs were reported for each quarter following a CV event, for up to 36 months after the first CV event. Results: In total, 38,609 CHD-RE patients were included, mean age 57 years, 31% female. CABG, myocardial infarction, and percutaneous coronary intervention were the most frequent and most expensive first CV events, accounting for >75% of all first CV events with mean first quarter costs ranging from $17,454 (nonfatal transient ischemic attack) to $125,690 (fatal CABG). Overall, 15% of those with a first CV event went on to have a second event during the 36-month study period with mean first quarter nonfatal and fatal costs similar to first event levels. Third CV events were rare, happening in less than 3% of patients. Conclusion: CV events among CHD-RE patients were costly regardless of sequence, averaging $47,433 in the first 90 days following an event and remaining high, never returning to preevent levels. When fatal, first CV event costs were 1.2 to 2.9 times higher than when nonfatal. Keywords: coronary heart disease risk equivalent, economic burden, subsequent CV event, fatal CV event